A Comparative Study of Ex-Combatant Reintegration in the African Great Lakes Region : Trajectories, Processes, and Paradoxes - Rhea, Randolph Wallace (World Bank, Washington, DC, 2016)
This report is structured in three parts. Part one is a summary document, including: (i) an executive summary (ii) an introduction; (iii) a review of core concepts of reintegration that will be referred to in this study; (iv) a meta-analysis of reintegration process¬es in the Great Lakes Region (GLR) vis-à-vis the conceptual discussion; and (v) conclusions to the summary document. Part two (annex one) comprises an in-depth review and analysis of data on the reintegration process-es of ex-combatants across the GLR. Part three (annex two) is an in-depth analysis of community dynamics across the GLR. In brief, part one of the study is a meta-analytical and knowledge-focused piece that reflects more broadly on the detailed analysis of the datasets presented in annexes one and two, therefore, this part can be read as a freestanding report. However, it’s worth noting that any reading will benefit significantly from exploring the detailed findings in annexes one and two.